C-reactive protein versus procalcitonin. Simillar but different biomarkers in the assessment of an infection - Tyniec, Mateusz; Lewicki, Marcin; Morshed, Kamal; Bojarczuk, Katarzyna; Smoleń, Agata Barbara (Journal of Education, Health and Sport, 2018)
Markers of systemic inflammation and bacterial infection such as C-reactive protein (CRP), and procalcitonin are commonly evaluated parameters in everyday medical practice. They are useful in quick assessment of patients condition, and the utility of CRP and procalcitonin as a marker of infection has been confirmed. An ideal marker of an inflammatory reaction should take into account many features. It should be remembered that we can not always choose one, more valuable biomarker. Interpretation of the results depends on numerous factors such as clinical status, weight and age. Both markers have their limitations. Early inflammatory disease diagnosis, properly implemented effective antibiotic therapy can contribute to the reduction of mortality.